Shift work and mental health sickness absence: a 10-year observational cohort study among male production workers - Giny Norder; Corné AM Roelen; Ute Bültmann; Jac JL van der Klink (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: Epidemiological studies investigating mental-health-related sickness absence (SA) among shift workers are lacking. This 10-year observational study investigated the risk of mental health SA among shift compared with day workers. METHODS: The data of 5826 male production workers were used for analyses: 4288 (74%) shift and 1538 (26%) day workers. The risk of mental health SA was analyzed with Cox regression analysis. Hazard ratios (HR) and 95% confidence intervals (95% CI) were adjusted for age and occupational grade. RESULTS: During a 10-year follow-up, 351 shift workers and 126 day workers had incident mental health SA. The risk of mental health SA did not differ (HR 1.03, 95% CI 0.84-1.26) between shift and day workers. Among shift workers, the risk of SA due to mood disorders (HR 1.87, 95% CI 0.73-4.76) was non-significantly higher than among day workers. A total of 96 shift workers and 21 day workers had recurrent mental health SA. The risk of recurrent mental health SA did not differ (HR 1.04, 95% CI 0.62-1.74) between shift and day workers. CONCLUSION: The risk of incident and recurrent mental health SA did not differ between shift and day workers.